TEORI GENERATIF-TRANSFORMATIF NOAM CHOMSKY DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA ARAB - Permata, Bagus Adrian (STAIN Kediri, 2015)
Language, as a tool of communication, attracted serious attention from linguists who formulate theories of language. Noam Chomskys’s generative transformative theory, among others, is believed to have put impacts on the development of linguistics. The theory suggested that language skills are a congenital human potential (innate) rather than a nature product. This article examines the relevance of generative transformative theory with Arabic learning as a foreigh language. It argued that the theory is reasonably though not fully relevant inthis context. The reason is that Arabic contains universal characteristics as any other languages in the world.Keywords: Teori Bahasa, Generatif-Transformatif, Bahasa Arab sebagai Bahasa Asing